Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 11 - Rational Expressions and Functions - Chapter Test - Page 707: 16



Work Step by Step

As we are given that $\frac{4b-2}{3b}+\frac{b}{b+2}$ LCD $= 3b(b+2)$ $=\dfrac{4b-2(b+2)}{3b(b+2)}+\dfrac{(3b)b}{3b(b+2)}$ After simplifications, we get $=\dfrac{(4b-2)(b+2)+b(3b)}{3b(b+2)}$ $=\dfrac{4b^2+8b-2b-4+3b^2}{3b(b+2)}$ $=\dfrac{7b^2+6b-4}{3b(b+2)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.